Understanding lifecycle trend of colour and trim for car interior design / Faten Ezrin Azhar - Ezrin Azhar, Faten (2016)
Car design is the field involved in the improvement and development of the visual appearance of the physical form. In car design team, the task has been divided into 4 main aspects which is exterior design, interior design, CAS and Model. In this thesis, the focus has been given at the interior design through colour and trim. The colour and trim in car design consider the element of aesthetic, ergonomic and technical. Moreover, the aspect of colour and trim which is material, the designer and design team responsible in researching, designing and developing of the whole entire styling of the form. The aim of this study is focuses on understanding lifecycle trend of colour and trim for car interior design. Nowadays, car design is not only be attractive in exterior design, but design is able to comfort and pleasant feeling to the users while in interior aspects. However, some of interior designs have difficulty to provide comfort and pleasant feeling even emotion to its user while interacting with the car. In this context, colour refers to aspect that creates combination of intensity, and contrast to give the car a unique interior environment experience. Trim is known as material using in car design, therefore to create a good quality perception and a customer desire by the knowledge of material and surfaces treatments. This study analyze how the colour and trim can be used as a strategic tools to make car design stands out for it trends. To achieve the aim and objectives in this study, a mixed method has been chosen as the research method for the data collection. By using images and colours through survey questionnaires, data was collected among industrial design students at the Universiti Teknologi MARA (UiTM) and practitioners in Proton and Perodua. The frequencies distribution and Pearson correlation analysis in SPSS software were used to analyze the survey data. Furthermore, content analysis was used to analyze the existing literatures and information. Consequently, it can be concluded that the information derived in this research can be used as a guideline for colour and trim, and strategic tools to predict the trends for car design. Additionally, the element of expression as interpreted by designer have a great ability to provide positive influence to the user. Also, results derived from this study answered the hypotheses made for this study which is "Understanding lifecycle trend of colour and trim for car interior design."